佛教與慈善 ：探討新加坡佛教實踐與社會現代化的關係 = Buddhism and charity : the study of Buddhist practices in relation to Singapore modernism - 林煇智 Lim, Daryl Hui Zhi (2014)
佛教是新加坡五大宗教信仰之一。根據新加坡統計局2010年的官方統計，佛教是新加坡宗教信徒數量最多的宗教。但是，自國家開埠以來，佛教隨著新加坡社會的發展已經歷了不同層面的衍變。國家在整體上的改變主要以走向現代社會為主。政府在多方面以西方思想模式為參照，試圖把國家帶入一個嶄新的階段。在這樣的前提下，人民的共同意識與價值觀也會隨著社會的變遷而改變，這些現代意識以及“新”價值觀的建立逐漸影響宗教在生活上所扮演的角色， 從而使國人對於宗教的教誨產生了另一種詮釋。¬ 這些外來的西方思想新潮在一定的程度上導致信徒對於佛教法門修行的改變。因此，新加坡佛教信徒在形式上更偏向於實踐修行，如慈善事業、教育傳承、賑災救濟等。這些現象也迎合了當代“人間佛教 ”在佛教界的發展。以新加坡佛教界的歷史脈絡來看，佛教與社會之間的長久關系也造成了“人間佛教”在新加坡佛教的普及與認可。由於“人間佛教”所涉及的范圍與社會緊密相聯，因此佛教信徒在受到社會內外無形力量的推拉下，推動了新加坡佛教在實踐與人間化的發展。本文將針對上述所談到的現象,探討新加坡社會在現代化過程中如何影響新加坡佛教慈善事業的發展，從而推論兩者之間在整個大環境的相互關系。同時，也將對新加坡佛教居士林林長李木源居士進行一次訪談，詳細了解佛教在現代化道路上所面臨的一些具體問題與改變，為新加坡佛教走向人間化的論證加以闡述。Buddhism is one of the five major religions in Singapore. According to statistics released by the Department of Statistics of Singapore, Buddhism has the highest number of followers in Singapore as compared to other religion. However, along with the development of Singapore society, Buddhism has experienced many phases of change since the early years. Modernism is one of the main attributes towards the change in Singapore society. In the process, the government aims to build a modern society by learning from the West and inculcating Western ideologies to its people. Under such influence, the collective values and consciousness of the people will evolve as the society develops. These modern consciousness and values will lead to new religious interpretation, and thus affecting the role of religion in people’s daily life. To a certain extent, these Western ideologies will change the way Dharma is cultivated in Buddhism, whereby they become more inclined to Practice Dharma like Charity, Provision of Education, Relief Work, etc. These phenomenons also coincide with the development of modern “Humanistic Buddhism” teachings in the Buddhist Community. In the historical context of Singapore Buddhism, the popularization and approval towards “Humanistic Buddhism” can be traced from the long connection between Buddhism and Society. As such, due to the close relation between these two factors, the development of Buddhist Practice can be seen as a result of societal forces acting onto Buddhist followers. Based on the phenomenon stated above, this paper aims to explore the connection between Charity and Buddhism and how Modernism has influenced the development of Buddhism Charity in the Singapore society. The research will also include an interview with the President of Singapore Buddhist Lodge, Mr. Lee Bock Guan, where he shares his experience and specific issues faced during his work of charity in modern Singapore society.